1994
DOI: 10.1088/0953-8984/6/33/017
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic and anisotropic magnetoelastic interactions in heavy and light RCo2Laves phase compounds

Abstract: The thermal expansion and anisotropic magnetomiction of the R C q Laves phases were studied in the temperature range 4-500 K using the x-ray powder diffraction methcd.In the heavy RCo2 the magnetic moment of the itinerant d electron subsystem derived imm the magnetovolume effect was found to fit well with the magnetization curve of YCo2. A pronounced paraprocess above the metamagnetic m i t i o n has been observed when increasing the f-d exchange field. "%e type and temperature variation of the distortion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 24 publications
6
66
1
3
Order By: Relevance
“…DyðCo 12x Si x Þ 2 can be classified as a narrow domain wall system due to the fact that the ordering temperature is much smaller (compared to DyFe 2 ). Also, the anisotropy is large due to the magneto-elastic distortions taking place at the T C ; as the sample is cooled from high temperatures [17,18]. Therefore, it is quite possible that the present system exhibits domain wall pinning effect and consequently a large thermomagnetic irreversibility.…”
Section: Resultsmentioning
confidence: 90%
“…DyðCo 12x Si x Þ 2 can be classified as a narrow domain wall system due to the fact that the ordering temperature is much smaller (compared to DyFe 2 ). Also, the anisotropy is large due to the magneto-elastic distortions taking place at the T C ; as the sample is cooled from high temperatures [17,18]. Therefore, it is quite possible that the present system exhibits domain wall pinning effect and consequently a large thermomagnetic irreversibility.…”
Section: Resultsmentioning
confidence: 90%
“…Figure 1 shows their characteristic pattern of transitions with changing number of 4f electrons, assuming all the ions to be in their usual 3+ state. The paramagnetic high temperature parent cubic structure gives way to ferromagnetic (R = Pr, Nd, Sm) or ferrimagnetic (R = Gd, Tb, Dy, Ho, Er, Tm) ordered structures at phase transitions which are marked also by symmetrybreaking shear strains and positive volume strains [2][3][4][5][6][7]. The magnetism is dominated by the R sublattice, with essentially temperature-independent magnetic moments.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic ordering temperatures are proportional to the de Gennes factor, Figure 1. Summary of magnetic phase transitions in RCo 2 Laves phases; data for GdCo 2 , TbCo 2 , DyCo 2 , HoCo 2 and ErCo 2 from [3], data for PrCo 2 , SmCo 2 and TmCo 2 from [4], data for NdCo 2 from [7].…”
Section: Introductionmentioning
confidence: 99%
“…They usually have gigantic values of the magnetocaloric effect, magnetostriction and magnetoresistance [2][3]. Among these materials there are RCo2 compounds, in which there is a sharp dependence the magnetic phase transitions from the lattice parameters [5][6][7][8][9]. Transformation of the crystal and magnetic structure as a result of magnetic phase transitions in NdCo 2 on polycrystalline samples was studied in [1], with methods of X-ray and neutron diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…Transformation of the crystal and magnetic structure as a result of magnetic phase transitions in NdCo 2 on polycrystalline samples was studied in [1], with methods of X-ray and neutron diffraction. Temperature dependence of the magnetostriction constants λ 100 for RCo 2 was calculated by measuring the lattice constant in [1,8,10] and it was shown that λ 100 for NdCo 2 reaches very high values of λ 100 =-3.2·10 -3 . However there is no data about the temperature dependence of linear and volume magnetostriction induced by magnetic field in NdCo 2 .…”
Section: Introductionmentioning
confidence: 99%